Enhancing literacy competence of 5th-grade students at SDN 3 Kerticala through learning assistance - Nura, Darojatun (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
The Ministry of Education and Culture of the Republic of Indonesia has implemented Kurikulum Merdeka policy to improve the quality of education. This policy contains assessment points covering literacy and numeracy. One of the instruments used in this policy is Asesmen Kompetensi Minimum (AKM), a tool for teachers to analyze student learning outcomes. To help teachers improve student literacy, a team of Kampus Mengajar Program batch 5 at SDN 3 Kerticala carried out community service that focused on helping the learning process of class V students at SDN 3 Kerticala. In this community service, 12 students of SDN 3 Kerticala took part in a learning assistance program run by a team of students from the Kampus Mengajar program. Implementing community service activities is filled with activities that can increase student literacy and play an essential role in assisting teachers in measuring and assessing student achievement at AKM. Data from the trial results after the implementation of learning assistance shows that the percentage of students who achieve competency has increased compared to the results obtained before the assistance. During the implementation of the assistance program, it was found that students needed to achieve specific competencies optimally. These findings can encourage teachers to optimize teaching and learning strategies that align with students' needs and learning styles.